“A comida é o de menos”: as redes sociais dos migrantes brasileiros na Colômbia - Erazo, Diana Patricia Bolaños (2019)
The present dissertation is an anthropological study about the migration of Brazilian families to Colombia, specifically to the city of Cali, in the southwest region, a place that has established itself as an industrial center - home to the main multinationals in the country. The material that will be presented and analyzed here, is the result of an ethnography carried out between June 2014 and March 2018, with intervals in which contact was maintained through virtual social networks, as well as interviews made possible during some of the trips that members of these families made it to Brazil. In this research I try to understand how the food practices and the ethnographic events that revolve around them are used by the Brazilian migrants as mechanisms of insertion in Caleña society and as a form of identification processes. This use often has the intention of updating the Brazilian national identity, in others it is a strategy to reproduce domestically the pre-migratory lifestyle and to evoke feelings that surpass the physiological need to feed and, finally, as a way of establishing and to update transnational affective bonds. The issue of return will also be briefly worked out in this ethnography, since it is a fundamental part of the migration project, and also because some of the women I research are in the pre-return stage to Brazil.